Reflections of employed graduates on the suitability of their skills and knowledge for workplace-readiness - Mobarak, K. (South African Journal of Higher Education, 2019)
There is broad consensus amongst scholars and policy makers that the development of workplace-ready graduates requires a review of the teaching and learning strategies currently informing classroom learning. It has been argued that the curricula taught at higher education institutions should be compatible with industry requirements and expectations: this would not only ensure the livelihood of graduates, but also their viability in an increasingly competitive and changing labor market. Accordingly, academics have a duty to revise their approaches to teaching and learning to ensure that the graduate output will service graduate workplace-readiness. In light of the aforementioned realities, this study explored the opinions of employed graduates with regard to their workplace-readiness upon employment. The primary objective was to establish whether South African higher education institutions are producing graduates considered worthy and capable by the employment sector. The study is guided by the following three theories: moral hazard; economics of trust and information; and adverse selection. These theories elucidate the importance of inclusive stakeholder responsibility and accountability for the development of workplace-ready graduates. Twenty-four responses of employed graduates from eight South African higher education institutions were obtained by means of a questionnaire administered via a Google link. The study found that graduates generally did not feel adequately prepared for the workplace. The paper concludes that considerable more effort is required to align higher education curricula, and teaching and learning strategies with labour market requirements.